Sosialisasi dan Edukasi Kawasan Keselamatan Operasional Penerbangan (KKOP) pada Masyarakat Sekitar Bandar Udara Betoambari Bau-Bau - Arsyad, La Ode Muhamad Nurrakhmad; Soeparyanto, Try Sugiyarto (Vokasi Universitas Halu Oleo, 2023)
Bau-bau City is one of the cities in Southeast Sulawesi Province, which is also the gateway to this province; this encourages relatively rapid progress in Bau-bau City such as education, trade, economy, industry, tourism, transportation and other infrastructure. A significant impact of this progress in Bau-bau City from various fields is the rapid population growth due to the movement of people from different regions, resulting in settlements throughout Bau-bau City. With population growth continuing to increase, the land in the Betoambari Bau-bau Airport area, especially in the runway extension area, could be converted into residential housing or other economic activities, which would invite the presence of many people of course, this would be contrary to efforts to avoid the possibility of an accident occurring in the area along the runway. Almost all communities, individuals and groups have widely used drones, air balloons, lasers and kites. On the one hand, technology can provide more significant benefits to certain groups of society, both specific and general. Still, another side can make using tools resulting from this technology potentially lousy and threaten aviation security. This outreach aims to educate the community around Betoambari Bau-bau Airport regarding activities that can endanger flights so that things that threaten flights caused by community activities can be avoided. The socialization method used was exposure from resource persons and discussions with people living near the Betoambari Bau-bau Airport area. This socialization and education can be the first step to prevent the growth and development of unsafe behaviour and improve dangerous environmental conditions. They can change the mindset of the people around Betoambari Bau Bau Airport to avoid activities that could disrupt flight operations. Socialization participants were very enthusiastic about participating in this activity, especially when they saw the facts of plane crashes and criminal consequences, which refer to Law Number 1 of 2009 concerning Aviation. Keywords: Aviation Operational Safety Area